Adsorption of CuX2 (X = Cl-, Br-, and ClO4-) on a silica gel surface chemically modified with thiazolidine-2-thione from acetone and ethanol solutions - Dias, N. L. (Maik Nauka/interperiodica, 1999)
The isotherms of adsorption of CuX2 (X = Cl-, Br, ClO4-,) by silica gel chemically modified with thiazolidine-2-thione were studied in acetone (ac) and ethanol (eth) solutions at 25 degrees C. The following equilibrium constants (in 1 mol(-1)) were determined: a) CuCl2, 1.9 x 10(3) (ac), 1.6 x 10(3) (eth); b) CuBr2, 1.7 x 10(3) (ac), 1.2 x 10(3) (eth); c) Cu(ClO4)(2), 1.1 x 10(3) (ac), 1.0 x 10(3) (eth). The electron spin resonance spectra of the surface complexes indicate a tetragonal distorted structure in the case of lower degrees of metal loading on the chemically modified surface. The d-d electronic transition spectra show that for the ClO4- complex, the peak of absorption did not change for any degree of metal loading, and for Cl- and Br complexes, the peak maxima shift to higher energy with lower metal loading.